Enhancing the cultivation of Salicornia fruticosa with agroindustrial compost leachates in a cascade cropping system: evaluating the impact of melatonin application - Giménez, Almudena; Gallegos-Cedillo, Victor M.; Benaissa, Rachida Rania; Egea-Gilabert, Catalina; Signore, Angelo; Ochoa, Jesús; Gruda, Nazim S.; Arnao, Marino B.; Fernández, Juan A. (Frontiers in Plant Science, 2024)
Cascade cropping systems (CCS) utilize leachate from a primary crop to grow secondary crops and enhance the efficient use of water and fertilizers in areas with scarce water resources. A preliminary study investigated the effect of melatonin in a cascade cropping system to potentially improve plant tolerance to abiotic stresses. This study aimed to cultivate Salicornia fruticosa in this cropping system to reduce nutrient discharge and assess the impact of exogenous melatonin on Salicornia growth and quality. The CCS included a primary crop of Salicornia grown in an agro-industrial compost and or peat. Leachates from these media were used to cultivate the same plant once again in a floating system under four treatments: compost leachate (T1), peat leachate (T2), 100 % nutrient solution (NS) (T3), 50 % NS (T4) strength. Four concentrations of exogenous melatonin were applied in foliar spray: 0, 100, 200, and 400 µM. Melatonin application increased yield, with the highest values observed when plants were grown in T1. Water use efficiency was also maximized in T1 and with both 200 and 400 µM melatonin applications. The highest nitrogen use efficiency was achieved in plants grown in peat Con formato: Inglés (Reino Unido)leachate. The lipid membrane damage was assessed revealing that plants grown in compost leachate exhibited the lowest MDA values regardless of melatonin concentrations. The accumulation of some antinutritional compounds (nitrate, oxalate, and sodium) were the highest in those plants grown in compost leachate. Overall, shoots grown in peat leachate exhibited the best phytochemical profile (total phenol content, total flavonoids, and antioxidant capacity), with peak values in plants treated with 200 µM melatonin. These findings suggest that it S. fruticosa can be cultivated effectively cultivated using leachate from a previous crop in a floating system and that exogenous melatonin application enhances the yield and nutritional quality of Salicornia shoots.